Soil contamination of agricultural territories of Ukraine with benz(a)pyrene in the pre-war period as a criteria of background pollution in the post-war period when determining the dangerous consequences of military actions (Environment & Health, 2024)
The aim of the study is a retrospective analysis of the contamination of agricultural soils in different regions of Ukraine with benzo(a)pyrene, which occurred in the pre-war period, as a basis for determining the background level for the post-war period and establishing the dangerous role of military actions in the contamination.Materials and methods of the study: The work used sanitary-hygienic, bibliometric and analytical methods. The analyses were carried out using the results of scientific research works obtained in the laboratory of hygiene of carcinogenic factors of the State Institution «Institute of Hygiene and Medical Ecology named O.M. Marzieiev» (nowadays is the Institute of Public Health) of the National Academy of Medical Sciences of Ukraine over the past ten years has received recognition in scientific research devoted to carcinogenic substances of different classes, including: priority surfactants in household and food products of the plant-based campaign. The work was carried out under the supervision of Professor N.Ya. Yanisheva, I.O. Chernichenko and Doctor of Medical Sciences I.S. Kireeva.Results: An analytical examination of carcinogenic hazard problem, environmental pollution, shows that in the territory of Ukraine, including agricultural areas, in the pre-war period, soil pollution with carcinogenic substances of the surfactant class was consistently observed, the concentrations of which exceeded the maximum permissible concentrations, but did not always reach levels that are dangerous due to the translocation effect.It was shown that military actions taking place on the territory of Ukraine in the last few years are accompanied by the emergence of numerous additional sources of environmental pollution with carcinogens of the specified class. Particularly dangerous in this regard are the movement of military equipment, fuel spills and numerous fires of varying intensity. This indicates the danger of increasing general soil pollution and its risk to agricultural products grown in these conditions.Conclusion: in the near future, the existing pollution, which recorded in the pre-war period, is a certain background level of content in soils of cyclic aromatic hydrocarbons and its indicator indicator benzo(a)pyrene for the future determination of the contribution of military actions to environmental pollution and its danger to the population.
Keywords: soil; benzo(a)pyrene; polycyclic aromatic hydrocarbons; food plants; background level; influence of military actions